The Influence of Emotional Intelligence on Consumer Decision-Making: Insights from Recent Studies - Kalliampakou, Ioanna; Antonopoulou, Hera (Technium Social Sciences Journal, 2025)
This paper investigates the complex interplay between emotional intelligence (EI) and consumer decision-making processes. It defines and discusses the key elements of emotional intelligence, including emotional awareness, emotional facilitation, emotional knowledge, and reflection. The study explained how emotions, through all stages of the decision process—from problem recognition to information search, evaluation of alternatives, purchase decision, and finally, post-purchase evaluation— metabatically affect consumers' preferences, judgments, and behaviors. It tackles the interface between psychological variables, habitual behaviors, and external influences modulating consumer choices. The paper will review the theoretical frameworks of trait emotional intelligence theory and the ability model and discuss both qualitative and quantitative methodologies used in the study of EI and consumer behavior. These findings underline the impact of EI on consumer outcomes and shed light on its implications in marketing strategies that include personalized experiences and emotional data analysis. The paper finally provides some practical recommendations on how to integrate EI into business strategies and infers further research directions regarding the evolving role that emotional intelligence could assume in consumer behavior, including the impact of digital emotional intelligence and authenticity.